Enhancing Company Value through Customer Loyalty in Umrah Travel Agencies - Ryan Firdiansyah Suryawan; Aminullah Assagaf; Suyanto; Sukesi; Slamet Riyadi (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Indonesia's rapidly expanding Umrah travel industry is currently facing challenges such as intense competition, demographic shifts, service quality issues, and declining customer trust. To address these concerns and enhance customer loyalty, trust, and corporate value, Umrah agencies are encouraged to improve their service quality, implement effective digital marketing strategies, strengthen customer relationship management (CRM), and increase transparency in service delivery. In response to these industry dynamics, this study aims to investigate the mediating role of customer satisfaction, broaden the conceptual dimensions of brand image, develop new CRM indicators, and analyze the influence of trust, service quality, and organizational culture on customer loyalty. Using a quantitative research approach, data were collected from 320 Umrah pilgrims who had used the services of 15 Umrah travel agencies operating in Jakarta, Bogor, and Depok. Data collection was conducted via structured questionnaires, and analysis was carried out using linear regression, the Sobel Calculator, and SPSS 25 software. Findings reveal that customer relationships significantly enhance satisfaction, with the role of ustaz and pilgrims' experiences proving crucial. Trust, reflected through the muthawif's role, also positively influences satisfaction. Notably, the study introduces a new perspective by incorporating experience-based indicators from pilgrims, ustaz, and muthawif, offering valuable insights for improving agency marketing strategies.